Oral and Gastrointestinal Sensing of Dietary Fat and Appetite Regulation in Humans: Modification by Diet and Obesity - Little, Tanya J.; Feinle-Bisset, Christine (Frontiers in Neuroscience, 2010)
Dietary fat interacts with receptors in both the oral cavity and the gastrointestinal (GI) tract to regulate fat and energy intake. This review discusses recent developments in our understanding of the mechanisms underlying the effects of fat, through its digestive products, fatty acids (FA), on GI function and energy intake, the role of oral and intestinal FA receptors, and the implications that changes in oral and small intestinal sensitivity in response to ingested fat may have for the development of obesity.